Ice Velocity Data from Ice Stream C, West Antarctica - Anandakrishnan, Sridhar (IEDA: US Antarctic Program Data Center, 2001)
Abstract: Ice velocity data from ice stream C, including the body of the ice stream and its area of onset, are available. The investigator calculated velocities from precise ice displacement measurements made with a geodetic-quality Global Positioning System (GPS). These ice displacement measurements accompanied seismic experiments aimed at understanding controls on the flow of ice streams in west Antarctica. An understanding of ice stream flow is essential to predicting the response of the West Antarctic Ice Sheet to future climate change. Data are available in ASCII format via ftp.